2004
DOI: 10.1227/01.neu.0000103420.53487.79
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of the Human Cochlear Nerve and Its Role in Microvascular Decompressions for Tinnitus

Abstract: The tonotopic organization of the cisternal segment of the cochlear nerve has an oblique rotatory structure as a result of the rotatory course of the cochlear nerve in the posterior fossa. Knowledge of this tonotopic organization of the auditory nerve in its cisternal course might benefit surgeons who perform microvascular decompression operations for the vestibulocochlear compression syndrome, especially in the treatment of unilateral severe tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 51 publications
2
46
0
1
Order By: Relevance
“…Hamartomas of internal [4], vascular loops [14] and osteomas [7] of internal acoustic meats were reported as a cause of tinnitus. De Ridder et al [8] showed that decompression of the vestibulocochlear can be effective in treating unilateral tinnitus. The gold standard technique for diagnosis of acoustic neuroma is magnetic resonance imaging [6].…”
Section: Discussionmentioning
confidence: 99%
“…Hamartomas of internal [4], vascular loops [14] and osteomas [7] of internal acoustic meats were reported as a cause of tinnitus. De Ridder et al [8] showed that decompression of the vestibulocochlear can be effective in treating unilateral tinnitus. The gold standard technique for diagnosis of acoustic neuroma is magnetic resonance imaging [6].…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular and cochlear nerves fuse to form the 8th CN closer to brain stem. 22 The introduction of MR imaging has permitted better visualization of the CPA and IAC and is the method of choice for evaluating the eighth CN in patients with audiovestibular symptoms. 23,24 Advances in MR imaging techniques and application of special sequences have enabled increased spatial resolution and more detailed analysis of the CPA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that tinnitus results from abnormal neuronal activity arising at some point along the auditory pathways which is interpreted as sound at a cortical level [7][8][9]. This abnormal neuronal activity is hypothesized to be the neural correlate of tinnitus, which is considered to be an auditory phantom phenomenon, similar to central neuropathic pain, due to neural plasticity in response to total or partial deafferentation somewhere along the auditory tract [7,[10][11][12]. Animal and human studies have provided some evidence for this theory [5,9,10,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%